Workshop Pengolahan Data dengan Software SmartPLS Untuk Data Primer dan Sekunder dalam Riset - Sari Rahmadhani; Abdullah Abdullah; Andi Kartika (Panggung Kebaikan : Jurnal Pengabdian Sosial, 2024)
Understanding data processing for young researchers such as students is crucial to completing the final assignment. An important phase in determining research results after data collection in the field is completed is the data processing stage. This stage is often an obstacle for novice researchers due to the limited development of materials from lectures that have been attended previously. Therefore, this community service becomes a medium for solving problems, namely by holding data processing training carried out in the form of a workshop. This data processing workshop is used for data collected through secondary data and primary data which is carried out in providing materials and practices. This workshop uses the SmartPLS software tool, starting with an introduction to the software, terms of use, and data processing practices. This activity is carried out within the STIE Totalwin environment, namely by forming a community service team as a resource person and the activity implementation committee. The training that was carried out can be followed well. The implementation of the data processing workshop can be carried out and run smoothly. The benefits of this activity are felt by all parties involved in this workshop.